Pig production and risk exposure: A case study in Hung Yen, Vietnam - Nguyen Thi Thu Huyen; Pham Van Hung (2016)
The effects of direct and indirect input factors on pig productivity and its production risk in Hung Yen, Vietnam, were investigated. In using a moment-based approach, a Cobb-Douglas production function was applied to capturing mean, variance, and skewness effects. The results of this study showed that the expenditure for feed and time length of production reduced both the variation in productivity and downside risk, whereas an expanding production scale increased both the variation in productivity and downside risk.